Technical assessment of whole body angiography and cardiac function within a single MRI examination. Issue 6 (June 2015) - Gandy, S.J.; Lambert, M.; Belch, J.J.F.; Cavin, I.D.; Crowe, E.; Littleford, R.; Macfarlane, J.A.; Matthew, S.Z.; Martin, P.; Nicholas, R.S.; Struthers, A.D.; Sullivan, F.; et al.
Abstract : Aim: To evaluate a combined protocol for simultaneous cardiac MRI (CMR) and contrast-enhanced (CE) whole-body MR angiography (WB-MRA) techniques within a single examination. Materials and methods: Asymptomatic volunteers ( n  = 48) with low-moderate risk of cardiovascular disease (CVD) were recruited. The protocol was divided into four sections: (1) CMR of left ventricle (LV) structure and function; (2) CE-MRA of the head, neck, and thorax followed by the distal lower limbs; (3) CMR LV "late gadolinium enhancement" assessment; and (4) CE-MRA of the abdomen and pelvis followed by the proximal lower limbs. Multiple observers undertook the image analysis. Results: For CMR, the mean ejection fraction (EF) was 67.3 ± 4.8% and mean left ventricular mass (LVM) was 100.3 ± 22.8 g. The intra-observer repeatability for EF ranged from 2.1–4.7% and from 9–12 g for LVM. Interobserver repeatability was 8.1% for EF and 19.1 g for LVM. No LV delayed myocardial enhancement was observed. For WB-MRA, some degree of luminal narrowing or stenosis was seen at 3.6% of the vessel segments (involving n  = 29 of 48 volunteers) and interobserver radiological opinion was consistent in 96.7% of 1488 vessel segments assessed. Conclusion: Combined assessment of WB-MRA and CMR can be undertaken within a single examination on a clinical MRI system. The associated analysis techniques are repeatable and may be suitable for larger-scale cardiovascular MRI studies. Highlights: We report the use of whole body MR angiography and cardiac MR as a single examination. Healthy volunteers with elevated cardiovascular disease risk were scanned. Vessel segments and cardiac function were assessed by Radiologists and Physicists respectively. The protocol took an average of 51 minutes to complete, and analyses were repeatable. This combined cardiovascular MRI protocol will be used for better targeting of future interventions.